MIMO precoding and combining solutions for millimeter wave systems - Ahmed Alkhateeb; Jianhua Mo; Nuria González-Prelcic; Robert W. Heath Jr. (IEEE Communications Magazine, 2014)
Millimeter-wave communication is one way to alleviate the spectrum gridlock at lower frequencies while simultaneously providing high-bandwidth communication channels. MmWave makes use of MIMO through large antenna arrays at both the base station and the mobile station to provide sufficient received signal power. This article explains how beamforming and precoding are different in MIMO mmWave systems than in their lower-frequency counterparts, due to different hardware constraints and channel characteristics. Two potential architectures are reviewed: hybrid analog/digital precoding/combining and combining with low-resolution analog- to-digital converters. The potential gains and design challenges for these strategies are discussed, and future research directions are highlighted.
Keywords: adaptive signal processing; compass; mmWave